Effect of different sources of organic fertilizers on crop growth and yield of cabbage - Roshani Adhikari; Shambhu Katel; Pratiksha Khatri Chhetri; Pramod Simkhada; Prabina Chaudhari; Shubh Pravat Singh Yadav (Journal of Agriculture and Applied Biology, 2023)
Cabbage is (Brassica oleracea var. capitata) a popular leafy vegetable in Nepal, but depleted soil fertility and inefficient production techniques can limit productivity. To address this, we conducted a study in the Jumla district of Karnali Province, Nepal during the 2022 main cropping season. We evaluated the impact of different organic fertilizers on the growth and yield of cabbage using a Randomized Complete Block Design with seven treatments and three replications with the hybrid cultivar 'Green Coronet'. The treatments included Farm Yard Manure, Poultry Manure, FYM + Vermicompost, Vermicompost, Black Wonder, FYM + Poultry Manure, and Sheep Manure. The parameters, including plant height, stem diameter, leaf length and width, head weight, polar and equatorial diameter, head circumference, root and shoot weight, and weight of the head (g) of cabbage were taken for measurement. Our findings showed that organic fertilizers significantly influenced the growth and yield of cabbage, with Vermicompost showing the most potential as a nutrient source for achieving higher growth and yield. The Vermicompost treatment resulted in the largest size of cabbage head (1026 g), while the Farm Yard Manure and Poultry Manure treatments had limited impact. Our results suggest that the use of organic fertilizers such as Vermicompost can lead to higher cabbage production, improved soil fertility, and reduced reliance on chemical fertilizers and pesticides. This has significant implications for promoting sustainable agriculture practices, improving food security, and providing economic benefits for farmers and communities in Nepal and beyond.